Reuse of residues and wastes of animal husbandry in a federal institution in Northern Tocantins: case study - Moreira, Wislayne Aires; Souza, Rogério Pereira de; Silva, Márcia Regina; Sellitto, Miguel Afonso (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
This article describes a case study on waste disposal in the sector bird and pig of an institution in northern Tocantins. The research question is how to optimize the disposal of waste from the bird and pig sector. Initially, we present a theoretical review of waste, which lack understanding about the subject and the challenges inherent waste. The following describes the case, according to information gathered by researchers with the institution studied. We describe the facts, investigate the causes that originated them and proposes improvements for the disposal and treatment of waste.